Associations of low levels of air pollution with cardiometabolic outcomes and the role of diet quality in individuals with obesity - Healy, Darren R. (Elsevier Inc., 2025)
Background: Exposure to air pollution is associated with adverse cardiometabolic health effects and increased mortality, even at low concentrations. Some of the biological mechanisms through which air pollution can affect cardiometabolic health overlap with health outcomes associated with diet quality and changes in diet.
Objective: The objective of this study is to investigate associations of air pollutants at average concentrations below the World Health Organization, 2021 air quality guidelines with cardiometabolic outcomes. Furthermore, potential interaction between air pollutants and diet quality will be assessed.
Methods: 82 individuals with obesity participated in a combined weight loss and weight loss maintenance study for a total of 33 weeks. A secondary analysis was conducted incorporating air pollution measurements. Data were analysed with linear mixed-effects models.
Results: A total of 17 significant associations were observed for single pollutants with 10 cardiometabolic outcomes, predominantly related to blood lipids, hormones, and glucose regulation. Diet quality, as measured by the Baltic Sea Diet score, did not appear to mediate the association of air pollution with cardiometabolic outcomes, however, diet quality was observed to significantly modify the association of PM2.5 with total cholesterol, and the associations of NO and O3 with ghrelin.
Discussion: These findings suggest that exposure to ambient air pollutants, especially particulate matter, at levels below World Health Organization, 2021 air quality guidelines, were associated with changes in cardiometabolic risk factors. Diet may be a personal-level approach for individuals to modify the impact of exposure to air pollution on cardiometabolic health.